Performance Comparison of AES and Blowfish Algorithm - Hendrawan Nur Majid; Trihastuti Yuniati; Dedy Agung Prabowo (Universitas Multimedia Nusantara, 2026)
The rapid advancement of communication and data storage technologies requires security systems capable of protecting sensitive information from cyber threats. Symmetric cryptography algorithms such as AES and Blowfish are widely used, although they exhibit different performance characteristics. This study compares both algorithms based on processing time, memory usage, and throughput on .txt, .pdf, and .zip files. The testing was conducted through a Python implementation using ECB and CTR modes. The results show that AES consistently outperforms Blowfish in terms of speed and throughput. For large files, AES using ECB mode reaches a throughput of 1128.42 MB/s, significantly higher than Blowfish using ECB mode at 92.26 MB/s, with faster encryption time as well, AES using ECB mode within 0.075 seconds while Blowfish using ECB mode within 0.928 seconds. The decryption process shows similar results, where AES using CTR mode achieves 546.70 MB/s, while Blowfish using CTR mode reaches only 81.59 MB/s. Overall, AES is more suitable for fast encryption-decryption on large-scale data processing, whereas Blowfish is more appropriate for small files or low-complexity applications.